2016
DOI: 10.1002/jsfa.8052
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteome analysis of egg yolk plasma proteins during storage

Abstract: It is likely that the increased degradation of protease inhibitors such as ovoinhibitor and α -macroglobulin-like protein 1-like during prolonged storage lead to an imbalance of protease and antiprotease in egg yolk, which may play a key role in the degradation of egg yolk proteins. These findings will provide an insight into the effects of storage on egg yolk protein changes and give a deeper understanding of the deteriorative process of chicken egg yolk. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Ovalbumin is one of the most abundant proteins in egg yolk plasma ( Mann and Mann, 2008 ). Ovalbumin transports from egg white to yolk during long-time storage ( Gao et al., 2017 ). Only 1 protein spot was identified as ovalbumin with molecular weight of 39.3 kDa at 18 ED in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ovalbumin is one of the most abundant proteins in egg yolk plasma ( Mann and Mann, 2008 ). Ovalbumin transports from egg white to yolk during long-time storage ( Gao et al., 2017 ). Only 1 protein spot was identified as ovalbumin with molecular weight of 39.3 kDa at 18 ED in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ovoinhibitor is a member of the Kazal family of protease inhibitors identified from egg white, which inhibits the activity of trypsin, chymotrypsin, subtilisin, elastase etc., serine proteases ( Oubre et al., 2003 ). Ovoinhibitor protein spots were detected in unfertilized egg white and egg yolk during storage and also in fertilized egg white during incubation ( Qiu et al., 2012 , Wang and Wu, 2014 , Gao et al., 2017 ). In this study, the MW of the identified ovoinhibitors was lower than their theoretical value suggested that the proteins degraded to keep the activity of serine protease which degrade macromolecular nutrients to support the growth and development of chicken embryo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic analysis is a powerful technique for investigating protein expression patterns, and has been used for chicken in several studies (Cao et al, 2012;Zhang et al, 2015;Desai et al, 2016;Gao et al, 2016;Li et al, 2016a,b). Skeletal muscle is an essential component of the animal body and its mass directly correlates with meat production (Güeller and Russell, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Comparative proteomics offers the possibility to analyze the differential expression patterns of all proteins in the same tissue at specific times and under specific environmental conditions. Several studies of chicken egg yolk proteome [6,7] and comparative proteomics analyses [2,8,9] have profiled its protein patterns in different states. The egg yolk protein profile compared to other poultry species remains unknown.…”
Section: Introductionmentioning
confidence: 99%